Assessment of Lead Levels in Dust and Date Palm ( Phoenix dactylifera L.) in 6-10 Year-old School Children Environment in Riyadh City, Saudi-Arabia - Bounessah, M.; Al-Shayeb, S.M.; Al-Ghefaili, K.M.; Abdulfatah, B. (Asian Journal of Chemistry, 2010)
To assess lead levels in the school environment of 6-10 year-old children in Riyadh City, swept-dust, soil and date palm (Phoenix dactylifera L.) leaflets were obtained from 55 schools located in a 35 km section passing through the city centre. The study area was divided into eastern, central, western and rural sections, the central area (city centre) being the section where the impact of environmental lead pollution is known to be the highest. Swept-dust samples were obtained from the inside and outside of school buildings in order to assess the extent of lead migration from streets into classrooms. Hence, samples were collected from school entrance (SCL1), school playground (SCL2), first floor (SCL3) and second floor (SCL4) of each school building. Soil and date palm (Phoenix dactylifera L.) leaflets were taken from the inside perimeter of each school. The leaflets were divided into washed (LFWS) and unwashed (LFUW) subsamples. Soil samples were collected from the top 5 cm of soil (SLA) and also at a depth of 30 cm, close to the date palm trees (SLB). After digestion with concentrated nitric acid at 80°C,. the samples were analysed for lead by flame atomic absorption spectrophotometry. The results showed that lead distribution is a reflection of traffic density and pollution from automotive emissions. Analysis of variance showed that mean lead concentrations for all variables in the city centre, were significantly different from those of the eastern and western sections. The dust-Pb means were found to be the highest in the city centre, i.e., 367 μg g-1, 273 μg g -1, 253 μg g-1 and 214 μg g-1 (from SCL1 to SCL4). These are higher compared with the eastern section (131 μg g-1, 103 μg g-1 , 117 μg g-1 and 130 μg g-1) and the western section (164 μg g-1, 135 μg g-1, 129 μg g-1 and 135 μg g-1). Lead pollution in the city centre was also reflected in unwashed (east = 20 μg g-1, centre = 40 μg g-1, west = 27 μg g-1, rural = 15 μg g-1) and washed leaflets (east=9 μg g-1, center = 18 μg g-1, west = 11 μg g-1, rural=7 μg g-1). Lead levels in unwashed leaflets showed a significant correlation with washed leaflets (0.77) but a poor correlation with SLB (0.32), suggesting metal absorption from the atmosphere. From this study, it is concluded that in spite of the dilution of windblown inhalable particulates and the reduction of Pb levels in gasoline, undue pollution from this metal is shown to exist in the 6-10 year-old schoolchildren environment in Riyadh city centre.